2018
DOI: 10.1111/1747-0080.12406
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and developmental methodology for the SIMPLE approach: A Systematised, Interdisciplinary Malnutrition Pathway for impLementation and Evaluation in hospitals

Abstract: Systematised, delegated, and interdisciplinary nutrition care activities are realistic in at least some settings. A model is now available to provide interdisciplinary care. Next steps including testing implementation will determine if this interdisciplinary model improves malnutrition care delivered in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(93 citation statements)
references
References 32 publications
1
91
0
1
Order By: Relevance
“…Consequently, there have been ongoing calls for greater healthcare team engagement and collaboration in nutrition care (Bell et al, 2018;Stone, 2013). Efforts to achieve this have included novel models of care addressing organizational culture (Tappenden et al, 2013) and interventions, such as protected mealtimes (Porter, Ottrey, & Huggins, 2017).…”
mentioning
confidence: 99%
“…Consequently, there have been ongoing calls for greater healthcare team engagement and collaboration in nutrition care (Bell et al, 2018;Stone, 2013). Efforts to achieve this have included novel models of care addressing organizational culture (Tappenden et al, 2013) and interventions, such as protected mealtimes (Porter, Ottrey, & Huggins, 2017).…”
mentioning
confidence: 99%
“…These projects include: BHIP: Behavioural Health Interdisciplinary Program [13] CHERISH: Collaboration for Hospitalised Elders Reducing the Impact of Stays in Hospital [14]. The SIMPLE Approach: A Systematised, Interdisciplinary Malnutrition Pathway for impLementation and Evaluation in hospitals [15]. REACH: The Researching Effective Approaches to Cleaning Hospitals study [16] The following case summaries explore how each implementation project utilised and operationalised the i-PARIHS framework.…”
Section: Resultsmentioning
confidence: 99%
“…Chapple et al , recently reported that 71.5% of a dietitians workload in a neurosurgical setting is spent managing EN. With an increasing focus on high‐value health care and demand for dietetic services, the use of a nurse‐led feeding protocol has the potential to further reduce OOS for the ward dietitian and hence save time to facilitate the delivery of full scope or extended specialised nutrition care . Once fully embedded into ward nursing care this TFP has the potential to do the above.…”
Section: Discussionmentioning
confidence: 99%
“…An increased understanding of TF practices has the potential to improve patients’ nutrition outcomes and work efficiency of dietitians. With increasing focus on high‐value health care and reducing low‐value activities, the use of feeding protocols led by non‐dietetic staff presents an opportunity for systematised and interdisciplinary nutrition care, releasing time for dietitians to deliver full scope or extended specialised nutrition care . The aim of this pragmatic study was to evaluate the impact of a newly developed and implemented nurse‐led TFP on patients’ nutrition outcomes, dietetic efficiency, and nurses’ attitudes, practices and knowledge on nutrition support.…”
Section: Introductionmentioning
confidence: 99%